2022
DOI: 10.1038/s41398-022-01785-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral abnormalities following prenatal psychosocial stress are differentially modulated by maternal environment

Abstract: Prenatal stress (PS) is associated with increased vulnerability to affective disorders. Transplacental glucocorticoid passage and stress-induced maternal environment alterations are recognized as potential routes of transmission that can fundamentally alter neurodevelopment. However, molecular mechanisms underlying aberrant emotional outcomes or the individual contributions intrauterine stress versus maternal environment play in shaping these mechanisms remain unknown. Here, we report anxiogenic behaviors, anh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…Animals exposed to PNS showed significant behavioral differences that resemble specific psychopathologic domains, with reduced sociability, increased anxiety and anhedonic behavior. These data are in line with previous reports showing the negative effects of different paradigms of prenatal stress on behavior outcomes [28][29][30][31]. It is interesting that the cluster analysis used to identify vulnerable and resilient animals revealed that the tests related to anxiety and sociability had higher predictive importance than the depressive one.…”
Section: Discussionsupporting
confidence: 91%
“…Animals exposed to PNS showed significant behavioral differences that resemble specific psychopathologic domains, with reduced sociability, increased anxiety and anhedonic behavior. These data are in line with previous reports showing the negative effects of different paradigms of prenatal stress on behavior outcomes [28][29][30][31]. It is interesting that the cluster analysis used to identify vulnerable and resilient animals revealed that the tests related to anxiety and sociability had higher predictive importance than the depressive one.…”
Section: Discussionsupporting
confidence: 91%
“…The ELS used for the present studies was PD because poor paternal care or absence increases the risk of numerous negative outcomes associated with social and emotional health [ 62 ], including increased risk of psychopathology [ 63 ], substance abuse, delinquency, and susceptibility to other diseases [ 64 , 65 ]. It was robustly demonstrated that perinatal social stress, broadly, can adversely impact offspring’s behavioral development and conduct [ 66 , 67 , 68 , 69 ]. Children raised in stressful environments characterized by conflict, separation, and low attachment are more predisposed to behavioral problems [ 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of intrauterine stress biomarkers is fundamental in the context of early interventions targeting poor health outcomes prevention later in life. A growing body of research suggests the biological pathways, such as the glucocorticoid and pro-inflammatory pathways that could be the translators of an environmental experience into phenotypic changes mediated by the epigenome [1][2][3]. Molecular mechanisms related to cells plasticity, such as DNA methylation (DNAm) levels, may mediate the activation of pathways related to physiological stress due to its dynamic interaction with the environment [4,5].…”
Section: Introductionmentioning
confidence: 99%